Quality and stability of cooked sausages made from turkey meat affected by the white striping myopathy - Carvalho, Larissa Tatero; Giampietro-Ganeco, Aline; Malagoli de Mello, Juliana Lolli [UNESP]; Ferrari, Fabio Borba [UNESP]; Souza, Rodrigo Alves de; Souza, Pedro Alves de [UNESP]; Borba, Hirasilva [UNESP]; Trindade, Marco Antonio; Dominguez, Ruben; Lorenzo, Jose M. (Wiley-Blackwell, 2021)
White striping (WS) defect is described by the appearance of white striation in pectoralis major muscles. This study was aimed to develop a cooked sausage made from turkey breast meat with different degrees of WS myopathy (breasts with no striations NOR, fillets with striations 1 mm SEV). Physico-chemical properties, microbiological, and sensory characteristics were assessed. As the myopathy increased, there was an increase in the lipid content (from 1.67 to 2.73 g/100 g) and TBARs (from 0.147 to 0.229 at Day 0 and from 0.387 to 0.472 mg MDA/kg at 56 days of storage), and a decrease in the hardness of cooked sausages (686, 705 and 542 N for NOR, MOD, and SEV, respectively). During the storage (56 days at 4 degrees C), an increase in the thiobarbituric acid reactive substances (TBARs) values was observed in all samples studied, presenting NOR the lowest TBARs values. Regarding color parameters, the highest a* values were observed in MOD sausages (p > .05; between 6.6 and 6.88 in MOD versus 6.03 and 6.40 in the other two batches), whereas the highest b* values were found in SEV sausages (p < .05; between 6.15 and 6.67 in SEV versus <6.0 in the other two batches). Concerning sensorial analysis, all samples were well accepted (scores >7). The NOR and MOD samples had the same scores for overall acceptability (7.48-7.62), while the use of SEV meat produced a slight decrease (7.25; p < .05). Therefore, turkey breast fillets with WS can be used in the manufacture of cooked sausages without impairing the quality of the products obtained. Practical applications Consumers demand high-quality products. White striping myopathy (WS) is a defect that affects both the composition and appearance of turkey meat. Therefore, the use of meat that has this defect for the preparation of cooked sausages is an alternative for the meat industry. This allows the meat industry to be more competitive, since it allows the use of meat of low commercial value, but with excellent nutritional characteristics for the preparation of a meat product, and therefore allows to commercialize this meat with added value. With this in mind, the present study is proposed to observe the influence of the use of meat with WS in comparison with the use of normal meat on the quality of the processed sausages.